ANALISIS JUMLAH SUMBER DAYA MANUSIA UNIT AMC TERHADAP PENGAWASAN SISI UDARA DI BANDAR UDARA SUPADIO PONTIANAK - Devi Febriyanti Putri (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Oversight of flight safety at Supadio Pontianak Airport is the duty and responsibility of the Apron Movement Control (AMC) unit. The most important thing for the smooth running of Apron Movement Control (AMC) operational activities on the air side is the availability of sufficient human resources or personnel so that supervision on the air side can be carried out optimally. The purpose of this study is to determine the need for human resources and the scope of supervision of Apron Movement Control (AMC) personnel at Supadio Pontianak Airport. This study uses a descriptive qualitative research method. The data that has been obtained will be analyzed qualitatively and described in descriptive form. The data used in this research are primary data and secondary data in this study include interviewers with Apron Movement Control (AMC) documents and literature studies. Based on the research results it is known that in carrying out their duties and responsibilities, the Apron Movement Control (AMC) unit still lacks personnel. Tasks that are still not handled optimally, namely supervision of Ground Support Equipment (GSE) vehicles, and Grond Handling personnel, as well as recording of flight data, so what many violations occur because the focus of Apron Movement Control (AMC) personnel is focused on service aerobridge operation.